The Islamic Ideology of Indonesian Linguistic Politeness - Sri Minda Murni; Mutsyuhito Solin (Aceh International Journal of Social Science, 2013)
Abstract - This article is aimed at describing the ideology of Islam in the Indonesian linguistic politeness system. The population was the emails posted to the mailing list by the members of Indonesian Moslem Society in America (IMSA) and the topic of discussion was Islam. The reason for choosing the topic is that it has potential to reveal expressions of linguistic politeness even as it encourages participation of the members, since it is a topic of interest to everyone. The sample was the email threads triggered by an article entitled ‘Mendeteksi virus liberal’ (Detecting the liberal virus), which followed by four, more-focused topics of discussion derived from the first, chronologically:  Kaca retak (Cracked mirror), Apakah Islam Agama yang Sempurna? (Is Islam a Perfect Religion), Apakah status ke-Islam-an JJ? (Is JJ a good Muslim?); and Memutus Rantai Permusuhan (Breaking the chain of enmity) which cover 57 emails during the period of April 26, 2011 to Mei 16, 2011 and written by 25 members of the IMSA. The method of study was discourse analysis by following the procedure such as: a) Identifying the expressions of disagreement; b) Identifying politeness strategies used; c) Classifying the politeness strategies; d) Identifying dispreferred utterances; e) Classifying dispreferred utterances: and f) Finding out the ideology of Islam in Indonesian linguistic politeness system. The findings show that the politeness strategies used are: a) professing personal-inadequacy on the matter at hand; b) posing questions; c) referring to Al Qur’an/Al Hadits and the precedents set by other pious Muslims; and d) complimenting, honouring, and praying for one another. Dispreferred utterances include: a) those who complimenting themselves; b) those who criticize others, making jokes on others, gossiping others, and making the situation more critical; and c) those who threaten others. The ideology of Islam that lies behind linguistic politeness is: a) the ideology of “watawa shaubil haq watawa shaubish shabr’’, an Arabic phrase meaning ‘Muslims must point one another towards the truth and they must do it patiently’; b) The ideology that implies that linguistic  politeness is not only concerned with the present but is believed to have consequences for the hereafter; and c) The ideology which believe linguistic politeness does not merely concern communication and living in harmony with others, as previous theories suggest, but more importantly it concerns with keeping Muslim brotherhood and with one’s self-actualization as obedient to God. It is suggested for future researchers to compare the findings with data from oral communication.   Keywords    :   Islamic ideology,  Indonesian language, politenessPaper Type:    Research Paper